2017
DOI: 10.1111/jerd.12349
|View full text |Cite
|
Sign up to set email alerts
|

Surface changes of various bulk‐fill resin‐based composites after exposure to different food‐simulating liquid and beverages

Abstract: For restoration of the affected teeth in patients who consume acidic food and beverages, roughness and erosion of resin composites should be considered. All of bulk-fill resin-based composites except SDR may be suitable for restorations in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 32 publications
1
54
1
4
Order By: Relevance
“…Another cause of that finding is the acidic pH associated with the buffer capacity of the drinks that undoubtedly influence the degradation of the dental materials since pKa is related to the pH and buffering condition. It is widely known that the potential of beverages to degrade the surfaces depends not only on the pH, but also on its buffer capacity (23). The pH and buffering of the Coca Cola are low (23) in contrast to the citric acid found in the coffee and juice, that, as mentioned before, show better buffer capacity, and, in association with low pH, may affect the resistance of the Filtek Z350 to acidic solutions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another cause of that finding is the acidic pH associated with the buffer capacity of the drinks that undoubtedly influence the degradation of the dental materials since pKa is related to the pH and buffering condition. It is widely known that the potential of beverages to degrade the surfaces depends not only on the pH, but also on its buffer capacity (23). The pH and buffering of the Coca Cola are low (23) in contrast to the citric acid found in the coffee and juice, that, as mentioned before, show better buffer capacity, and, in association with low pH, may affect the resistance of the Filtek Z350 to acidic solutions.…”
Section: Discussionmentioning
confidence: 94%
“…The composite has ytterbium trifluoride in the composition that may keep the brightness of the surface with the release of soluble fluoride to the water (22). In addition, during the degradation process the molecule of water may diffuse into the polymeric network filling the microspaces between the chains, promoting the breakdown of siloxane link and the softening of the organic matrix (23). If hydrolytic degradation occurs, the reflection of light is jeopardized (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [16,20] Tanthanuch et al [21] reported an increase in surface roughness and a decrease in microhardness values, for the bulk fill composites stored in food simulating solutions and beverages for 28 days.…”
Section: Discussionmentioning
confidence: 94%
“…In their study on comparing the microhardness of various bulk fill composites (SDR, SonicFill, Tetric N-Ceram Bulk Fill, Filtek Bulk Fill) exposed to food simulating solutions and beverages, Tanthanuch et al [21] reported that the most significant decrease in microhardness values was observed with passionfruit juice having a high concentration of citric acid, whereas the bulk fill composite affected at most was found to be SDR.…”
Section: Discussionmentioning
confidence: 99%
“…3 Bulk-fill composites are newer restorative materials which are said to present improved cure, controlled polymerization contraction stresses and a reduced cuspal deflection; they are effectively photoactivated in layers up to 4 mm, and as such can be used in deep preparations. 4,5 A higher translucency observed in bulk-fill composites as compared to conventional resin composites enables superior light transmission, and thus better polymerization. A higher percentage degree of conversion (DC) displayed by bulk-fill composites is due to better light penetration, as the materials exhibit a reduced opacity.…”
Section: Introductionmentioning
confidence: 99%